Venture financing report as informational source of adoption of effective government decisions on innovation enterprises - Khomenko H.Yu. (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The research is devoted to the study of peculiarities and trends of the development of venture financing in Ukraine. The study clarifies the role of accounting and reporting of the enterprise in making management decisions regarding venture financing, and also founds that the provision of internal reporting on venture capital will allow investors to assess adequately the possibilities of obtaining dividends from the implementation of a venture project and the fulfillment of obligations on the securities of the enterprise-recipient. The analysis of the financial statements shows that the financial reporting indicators are rather generalized and therefore insufficient to formulate precise and substantiated conclusions on operations with venture financing as well as conduct the effective analysis of the financial condition of the enterprise. The solution of this problem is to improve existing financial reporting and to develop and formulate the package of internal accounting reporting on venture financing, whose purpose is to meet the needs of management personnel at all levels.